(untitled) (Research, Society and Development, 2020)
This paper aims to analyze what was and what is being produced about health practices in candomblé. For this, the integrative literature review was used. The search was performed using the keywords “candomblé” and “health” in Scielo, LILACS, MEDLINE, PubMed and Google Scholar databases. The research included articles published at any time (year), performed in Brazil and which discuss about health practices in candomblé. Thus, 10 articles were analyzed in this review. The five thematic categories that emerged were: health problems as a way to religion and therapeutic itineraries; conception of disease / illness and the boundary between the spiritual and the material; the health practices exercised and the importance of medicinal herbs; religion as a support network; and intolerance, access difficulties and ignorance by the formal Health System. It is concluded that the practices of candomblé are intrinsic to the health care of its practitioners and that the approximation of state equipment to places of worship - as with other religions - would be beneficial for both sides, expanding the performance of health team in the community and favoring integral and shared care of terreiro peoples.